Spontaneous stacking of electrospun conjugated polymer composite nanofibers producing highly porous fiber mats - Abdul Rahman, Norizah; Gulur Srinivas, Anupama Rao; Travas-Sejdic, Jadranka (Elsevier, 2014)
We produced novel composite nanofibers based on poly(6,6′-((2-methyl-5-((E)-4-((E)-prop-1-en-1-yl)styryl)-1,4-phenylene)bis(oxy))dihexanoic acid)/poly(lactic acid) (PDMP/PLA), using electrospinning technique. The composite nanofibers have a diameter in the range of 50–150 nm and present a novel morphology consisting of spontaneously stacked nanofibers creating a “wall-like” structure that then collectively form a “honeycomb” structure. As low as 0.5–1 wt% of the photoluminescent PDMP was able to produce this type of morphology. The pore size depends on the amount of PDMP incorporated in the nanofibers. The highly fluorescent and porous nanofibers mats provide good biosensing substrates. We provide evidence that the composite nanofibers can be used to construct a simple oligonucleotide (ODN) sensor, where capture probe ODNs (capODN) were covalently grafted onto the carboxylic acid functionalities of the composite nanofibers and the reporting ODN carries a reporting chromophore dye. The results indicate potential of such nanofiber mats as biosensor.